MEK1/2 inhibition decreases pro-inflammatory responses in macrophages from people with cystic fibrosis and mitigates severity of illness in experimental murine methicillin-resistant Staphylococcus aureus infection - De, Mithu; Serpa, Gregory; Zuiker, Eryn; Hisert, Katherine B.; Liles, W. Conrad; Manicone, Anne M.; Hemann, Emily A.; Long, Matthew E. (Frontiers in Cellular and Infection Microbiology, 2024)
Chronic pulmonary bacterial infections and associated inflammation remain a cause of morbidity and mortality in people with cystic fibrosis (PwCF) despite new modulator therapies. Therapies targeting host factors that dampen detrimental inflammation without suppressing immune responses critical for controlling infections remain limited, while the development of lung infections caused by antimicrobial resistant bacteria is an increasing global problem, and a significant challenge in CF. Pharmacological compounds targeting the mammalian MAPK proteins MEK1 and MEK2, referred to as MEK1/2 inhibitor compounds, have potential combined anti-microbial and anti-inflammatory effects. Here we examined the immunomodulatory properties of MEK1/2 inhibitor compounds PD0325901, trametinib, and CI-1040 on CF innate immune cells. Human CF macrophage and neutrophil phagocytic functions were assessed by quantifying phagocytosis of serum opsonized pHrodo red E. coli, Staphylococcus aureus, and zymosan bioparticles. MEK1/2 inhibitor compounds reduced CF macrophage pro-inflammatory cytokine production without impairing CF macrophage or neutrophil phagocytic abilities. Wild-type C57BL6/J and Cftrtm1kth (F508del homozygous) mice were used to evaluate the in vivo therapeutic potential of PD0325901 compared to vehicle treatment in an intranasal methicillin-resistant Staphylococcus aureus (MRSA) infection with the community-acquired MRSA strain USA300. In both wild-type and CF mice, PD0325901 reduced inflammation associated body mass loss. Wild-type mice treated with PD0325901 had significant reduction in neutrophil-mediated inflammation compared to vehicle treatment groups, with preserved clearance of bacteria in lung, liver, or spleen 1 day after infection in either wild-type or CF mouse models. In summary, this study provides the first data evaluating the therapeutic potential of MEK1/2 inhibitor to modulate CF immune cells and demonstrates that MEK1/2 inhibitors diminish pro-inflammatory responses without impairing host defense mechanisms required for acute pathogen clearance.